UNIVERSAL SENSITIVITY LIFI RECEIVER FOR DIGITAL LIBRARY - Annakodi, R.; Santhiya, P.; M.D, Shreedharan; M, Jeganathan (International Journal of Psychosocial Rehabilitation, 2018)
The main problem during the data transfer is security. In early days various data transferring techniques has been used like wired data transfer, wireless data transfer, satellite based data transfer and etc. But each techniques having various drawbacks like security, data transfer rate, data loss and etc. As mentioned above, the most important problem is the security and data breaching. Also various researches have been still going on for secured data transfer. In case of high secured data transfer there are various limitations like, one to one communication or need one authorized person to validate the secured data. This makes more time consuming too. So these technologies are still in research. In order to overcome these problems, in this project Light Fidelity (Li-Fi) has been introduced. It is a new technique to transfer secured data using lights. For light via data transfer LED (Light emitting diode) has been used in both transmitting and receiving end. From one PC to another PC data can be transferred through light. In early research the light will blink and flash during the time of data transfer that may irritate to the user during the data transfer. Also the upload speed is not getting match with the download speed, so that low data transfer rate will occur. There problems are overcome in this system like, light will not flash during the time of data transmission, continuous light emission will be transfer the data. Also upload speed is equal to the download speed, through this method data transfer rate will be more high.